Ideophones in Japanese modulate the P2 and late positive complex responses - Lockwood, Gwilym; Tuomainen, Jyrki (Frontiers in Psychology, 2015)
Sound-symbolism, or the direct link between sound and meaning, is typologically and behaviorally attested across languages. However, neuroimaging research has mostly focused on artificial non-words or individual segments, which do not represent sound-symbolism in natural language. We used EEG to compare Japanese ideophones, which are phonologically distinctive sound-symbolic lexical words, and arbitrary adverbs during a sentence reading task. Ideophones elicit a larger visual P2 response and a sustained late positive complex in comparison to arbitrary adverbs. These results and previous literature suggest that the larger P2 may indicate the integration of sound and sensory information by association in response to the distinctive phonology of ideophones. The late positive complex may reflect the facilitated lexical retrieval of ideophones in comparison to arbitrary words. This account provides new evidence that ideophones exhibit similar cross-modal correspondences to those which have been proposed for non-words and individual sounds, and that these effects are detectable in natural language.